SURAKARTA BERGERAK (REKONSTRUKSI SEJARAH PERGERAKAN DI SURAKARTA AWAL ABAD KE-20) - syamsul Bakri (Penamas, 2018)
ABSTRACT This research is the result of a historical research, which aims to reconstruct the emergence and growth of movement in Surakarta in colonial period. This study answers the questions of dynamics and movement in Surakarta, which include: (1) background factors of the dynamics and movement in Surakarta in colonial period, and (2) the form of dynamics and movement. The method used in this study is historical method, which consists of four stages, namely heuristic, source criticism, interpretation, and historiography. The historical paradigm used is that of John Tosh, i.e. to reconstruct history by understanding the social background and circumstances that cause the development of an event, and the direction of its changes. As for the reconstruction of the past, this study uses the model of the central circle. In this model, it is assumed that the incident at the center of the circle will have consequences in the vicinity. In turn, the center of the circle and the surrounding areas will lead to a new center around which will also result in new symptoms. The theory used is the theory of conflict, social movements, and resistance ideology. The use of the social theories is important for the study of history to expand in space (synchronous), in addition to remaining in the basic ground pattern of history that extends in time (diachronic). This study found historical facts that, in a piece of history of the movement in Indonesia, there are various factors and form of the dynamics of movement in Surakarta at colonial period. Dynamics and movement in Surakarta motivated by external factors (pressure from Western imperialism) and internal one (increasing struggle of indigenous organizations and modern media). The form of dynamics and movement in Surakarta are central circular, complex and interrelated in various fields, namely social and cultural sectors, agrarian, economic, political and religion. The results of this research have contributed knowledge to the discipline of history, especially in the exposure and reconstruction of a history fragment of the dynamics and movement of natives (indigenous people) in the revolt imperialism. In addition, the role of religion movement in forming a moving situation is found in this study. It indicates that this research can also contribute to the discipline of History of Islamic Culture.